"Breaking Up Is Hard to Do": The Formation and Resolution of Sister Chromatid Intertwines. Issue 3 (13th February 2015) - Baxter, Jonathan
Abstract: The absolute necessity to resolve every intertwine between the two strands of the DNA double helix provides a massive challenge to the cellular processes that duplicate and segregate chromosomes. Although the overwhelming majority of intertwines between the parental DNA strands are resolved during DNA replication, there are numerous chromosomal contexts where some intertwining is maintained into mitosis. These mitotic sister chromatid intertwines (SCIs) can be found as; short regions of unreplicated DNA, fully replicated and intertwined sister chromatids—commonly referred to as DNA catenation—and as sister chromatid linkages generated by homologous recombination-associated processes. Several overlapping mechanisms, including intra-chromosomal compaction, topoisomerase action and Holliday junction resolvases, ensure that all SCIs are removed before they can prevent normal chromosome segregation. Here, I discuss why some DNA intertwines persist into mitosis and review our current knowledge of the SCI resolution mechanisms that are employed in both prokaryotes and eukaryotes, including how deregulating SCI formation during DNA replication or disrupting the resolution processes may contribute to aneuploidy in cancer. Graphical Abstract: Highlights: Review of when SCIs are formed in cells during DNA replication. Review of the overlapping mechanisms that ensure the complete resolution of SCIs in mitosis. Discussion of how these types of SCIs could contribute to chromosomal instability phenotypes in cancer cells.